EXPLORING THE IMPACT OF INSULIN DEINTENSIFICATION ON BODY WEIGHT AND GLUCOSE CONTROL IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - Faizal, Nur Aflyn Fatinah; Hatah, Ernieda Md; Robert, Sarah Anne; See, Yeap Yoon; Azhari, Afifah; Adam, Noorlita (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Deintensification of insulin regimens and doses has potential to prevent overtreatment and hypoglycemia. This study aims to identify the characteristics and reasons for deintensification in Type 2 Diabetes Mellitus (T2DM) patients; to evaluate glycemic efficacy and to examine changes in body weight following deintensification and factors influencing these outcomes. METHODOLOGY A retrospective cohort observational study was conducted among T2DM patients from Hospital Tuanku Ja’afar and Hospital Canselor Tuanku Mukhriz. Data were collected from patient records receiving insulin deintensification from January 2020 to January 2024 using a data collection form with six sections. RESULT A total of 134 patients from two hospitals were included in this study, with 75 patients from HTJ and 59 patients from HCTM. The mean age was 57.25 ± 14.02 years, with an equal distribution of male and female participants. The majority were Malay (n = 69, 51.5%), followed by an equal number of Chinese and Indian (n = 32, 23.9% each), with most patients on a basal bolus regimen (n = 69, 51.5%), followed by a premixed (n = 63,47%) and a basal (n = 2,1.5%). The mean duration of diabetes was 17.54 ± 8.28 years. Baseline HbA1c was 9.38 ± 1.86% and most patients used insulin four times a day (n = 59, 44%). The mean total daily insulin dose decreased from 77.99 ± 30.18 units to 60.11 ± 25.39 units. Hypoglycemia events reduced from 98 to 11 episodes. The main reason for deintensification was hypoglycemic events (n = 98, 73.1%). HbA1c reduced from 9.38 ± 1.86% to 8.72 ± 1.78% (t (133) = 5.57, p <0.001), and weight decreased from 77.27 ± 15.83 kg to 75.80 ± 15.75 kg (t (133) = 6.19, p <0.001). Factors significantly associated with changes in HbA1c include baseline HbA1c (p <0.001), use of basal-only insulin (p = 0.002), and reduction in insulin injection frequency by one (p = 0.002) and two (p = 0.004) times per day. CONCLUSION Insulin deintensification significantly improves glycemic control and reduces body weight in T2DM patients. Key factors influencing these improvements include baseline HbA1c levels and the type and frequency of insulin used. Monitoring for signs of overinsulinization and hypoglycemia, particularly those with high HbA1c, is crucial for optimizing diabetes management.